APLIKASI FABRIKASI DIGITAL ARSITEKTUR STUDI DESAIN PARAMETRIK DIAGRAM VORONOI - Hendro Trieddiantoro Putro; Wiliarto Wirasmoyo (NALARs, 2020)
The development of technology and design methods in architecture continues, for example, parametric design methods and the application of digital fabrication technology to create models of representation and construction. Digital fabrication defined the process of manipulating objects using a CNC router, 3d printer, and laser cutter using a reduction or addition method. Studying digital fabrication technology is now a demand for academics and professionals in the field of architecture. Both architecture instructors and students are now required to increase their understanding and ability to process digital designs into scale-scale representation through a digital fabrication process.Through this research, researchers will describe the learning process of digital laser cut fabrication applications using parametric design methods, which are in the form of developing a Voronoi diagram-based design. Parametric design development will be carried out using Rhino software with Grasshopper. This research activity was carried out in the Department of Architecture FST Campus 2, University Technology of Yogyakarta. This research divided into several activities, namely the digital design process, the fabrication preparation process, and the installation or assembly of the model. Also, researchers will explain the obstacles or problems faced in each activity, as well as the opportunities and challenges of digital fabrication applications in architecture.The results of the study showed a clear process in each phase of the activity, and the explanation complemented by obstacles or problems encountered and problem-solving. Failures that occur in the fabrication process provide learning that digital design and digital fabrication are a unified, interconnected process. The opportunities and challenges of digital fabrication applications in the architectural world are further interesting considerations to discuss.